2019
DOI: 10.1101/789032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The microbiomes of seven lichen genera reveal host specificity, a reduced core community and potential as source of antimicrobials

Abstract: The High Andean Paramo ecosystem is a unique neotropical mountain biome considered a diversity and evolutionary hotspot. Lichens, which are complex symbiotic structures that contain diverse commensal microbial communities, are prevalent in Paramos. There they play vital roles in soil formation and mineral fixation. In this study we analyzed the microbiomes of seven lichen genera in two Colombian Paramos using 16S rRNA gene analyses and provide the first description of the bacterial communities associated with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 87 publications
0
5
1
Order By: Relevance
“…The bacterial community of reindeer lichens does not cluster together by host species, although values of beta diversity are significant between C. stellaris and C. stygia. Our results differ from previous studies which demonstrated that the bacterial community in lichens are host-specific (e.g., Bates et al 2011;Sierra et al 2020). found species-specific bacteria in three lichens with different growth forms: fruticose, crustose, and foliose.…”
Section: Absence Of Host-selectivity In Reindeer Lichenscontrasting
confidence: 99%
See 3 more Smart Citations
“…The bacterial community of reindeer lichens does not cluster together by host species, although values of beta diversity are significant between C. stellaris and C. stygia. Our results differ from previous studies which demonstrated that the bacterial community in lichens are host-specific (e.g., Bates et al 2011;Sierra et al 2020). found species-specific bacteria in three lichens with different growth forms: fruticose, crustose, and foliose.…”
Section: Absence Of Host-selectivity In Reindeer Lichenscontrasting
confidence: 99%
“…found species-specific bacteria in three lichens with different growth forms: fruticose, crustose, and foliose. Sierra et al (2020) also suggested bacteria host-specificity in seven genera of lichens with different thallus morphologies (Cora, Hypotrachyna, Peltigera and Sticta are foliose, and Usnea, Cladonia and Stereocaulon are fruticose). A possible explanation is that host-specificity is growthform-specific.…”
Section: Absence Of Host-selectivity In Reindeer Lichensmentioning
confidence: 96%
See 2 more Smart Citations
“…The preprint version of this manuscript has been deposited at bioRxiv-the preprint server for biology as: Sierra et al, 2019. The microbiomes of seven lichen general reveal host specificity, a reduced core community and potential as source of antimicrobials. doi: 10.1101/789032.…”
Section: Author's Notementioning
confidence: 99%